PTH-039 Preventing Post-endoscopic Retrograde Cholangiopancreatography (ercp) Pancreatitis: Changing Practice At A District General Hospital. (9th June 2014) - Elsayed, G; Cheung, MCM; Mansoor, M; Tonkin, J; Lindo, D; Gertner, D; Subhani, J
Abstract : Introduction: Post-ERCP pancreatitis (PEP) is one of the major endoscopic complications carrying 3.5% risk in unselected patients. Daycase ERCP is now the norm in the UK and emergency presentations with PEP may be expected. At Basildon Hospital, we sought to adopt ESGE guidelines (2010) 1 to prevent PEP with regards to: serum amylase testing, rectal non-steroidal anti-inflammatory (NSAID) and pancreatic duct (PD) stent use. Since March 2013, a protocol incorporating these recommendations was followed. Methods: A prospective audit between December 2012 to 2013 was performed to evaluate the effect of this management protocol. Data was collected on an audit proforma completed immediately following ERCP. Patient outcome was followed up via telephone on subsequent day or review of inpatient notes. Electronic records were searched for admissions within 2 weeks of ERCP. Results: 249 ERCP procedures were recorded over the 12 month period. 41% were male; 45% were performed as outpatient. Mean age was 68 years. Main indication was gallstones (60%). 224 amylase tests were performed on 139 patients. 27/139 patients had abnormal amylase (>1.5x upper limit normal (ULN) at 2–4 h or 3–5x ULN at 4–6 h). 14 were asymptomatic, 3 patients were admitted. Remainder with mildly abnormal amylase were managed without admission after clinical assessment. There were total 8 cases of pancreatitis (3.2%), all associated with significantly raised amylase, apart from one (inpatient) case with a late rise at 48 h. Pre-protocol, 1 patient developed pancreatitis after discharge from day case. NSAID use rose from 0 to 57% (14% contraindications), with no increased bleeding associated. PD stent insertion rose but remained infrequent, limited by technical feasibility. Pancreatitis rates did not significantly differ with prophylactic measures. Conclusion: This audit demonstrated the real-life practice of ESGE guidelines to assess for and reduce ERCP-related complications. Amylase measurement was feasible – raised levels correlated with PEP but 1 case had normal early amylase. The few admissions with asymptomatic raised amylase is offset by avoiding emergency admission with PEP. In this small study NSAID and PD stent did not improve complication rates and remain under-utilised, but likely will increase as experience grows. Reference: 1 Dumonceau JM et al . European Society of Gastrointestinal Endoscopy (ESGE) guideline: prophylaxis of post-ERCP pancreatitis. Endsocopy 2010;42:503-515 Disclosure of Interest: None Declared.